FMEA Approach in Risk Analysis of Main Engine Fuel System Maintenance: Case Study on The Express Bahari 1F - I Made Aditya Nugraha; Frengky Yeremias Malelak (Politeknik Negeri Padang, 2024)
The fuel system is one of the main engine support systems which is very important in the operation of the Express Bahari 1F main engine. Operation of the main engine requires special treatment of the components of the main engine to prevent failure during operation. The Failure Mode and Effect Analysis (FMEA) method is a method that can be used to identify the priority scale in maintaining a machine by evaluating the risk of failure occurring on the machine. This research uses FMEA analysis to determine the priority scale for maintenance of the Express Bahari 1F main engine fuel system. The identification results show that the injector, fuel filter and separator components are components that must be prioritized for maintenance. This type of maintenance is carried out by checking for dirty fuel which can cause the injector to operate less than optimally, cleaning deposits on the fuel filter cartridge on the fuel filter, and replacing a new separator if the separator performs poorly. It is recommended that other components be checked so that the main engine fuel system has good reliability.